2012
DOI: 10.2106/jbjs.k.01229
|View full text |Cite
|
Sign up to set email alerts
|

High-Flexion Total Knee Arthroplasty: Survivorship and Prevalence of Osteolysis

Abstract: After a minimum duration of follow-up of ten years, there were no significant differences between the two groups with regard to implant survivorship, functional outcome, knee motion, or prevalence of osteolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 11 publications
5
49
1
1
Order By: Relevance
“…However, there was no difference in satisfaction scores or the ''feel'' of the knee between the two implants, questioning the relevance of this degree of improved flexion. Furthermore, other studies have failed to demonstrate improved ROM, functional outcomes, or survival rates with the use of high-flex designs [21,24]. Our study found no differences between the high-flex and 10-year-old CR with regard to patient satisfaction and residual symptoms.…”
Section: Discussionmentioning
(Expert classified)
See 2 more Smart Citations
“…However, there was no difference in satisfaction scores or the ''feel'' of the knee between the two implants, questioning the relevance of this degree of improved flexion. Furthermore, other studies have failed to demonstrate improved ROM, functional outcomes, or survival rates with the use of high-flex designs [21,24]. Our study found no differences between the high-flex and 10-year-old CR with regard to patient satisfaction and residual symptoms.…”
Section: Discussionmentioning
(Expert classified)
“…Although daily activities such as ascending and descending stairs are known to require 90°to 120°of flexion, numerous studies have demonstrated knee flexion to rarely exceed 110°to 115°after a TKA [1,37,38], raising questions about the ability of modified implant designs to significantly increase these values. Although certain studies have demonstrated improved results regarding the degree of flexion achieved using high-flex implants, whether patients perceive this increase to be clinically significant remains controversial [21,24,42]. Thomsen et al [42], in a double-blind, randomized controlled trial of 36 patients undergoing one-stage bilateral TKA with a CR TKA in one knee and a high-flex TKA in the contralateral knee, demonstrated the high-flex TKAs to achieve a mean of 7°g reater knee flexion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Li et al [14] included the largest of the 18 randomized controlled trials on the subject. Although they found no significant differences between high-flexion and standard TKA designs in terms of range of motion, knee scores, patient's satisfaction, and complications, the types of high-flexion and standard implants used in the randomized controlled trial were limited to NexGen knee system (Zimmer, Warsaw, IN) (LPS-flex [4,6,11,[23][24][25][26][27][28][29][30] or CR-flex [3,7]) or P.F.C. Sigma knee system (RP-F [1,2,31,32] or CR 150 [33]).…”
Section: Discussionmentioning
confidence: 99%
“…Sumino et al [25] analyzed the change in range of knee flexion from preoperative values between high-flex group and standard group and found that improvement of preoperative flexion after TKA using high-flex prosthesis was similar to that of standard prosthesis. After a minimum duration of follow-up of ten years, Kim et al [39] found that there were no significant differences between NexGen LPS-Flex and NexGen LPS groups with regard to implant survivorship, functional outcome, knee motion, or prevalence of osteolysis. The conclusions of these studies were consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%